Penggunaan Media Sosial Terhadap Penguatan Moderasi Beragama - Muhammad Fadhlan; Nurul Hasanah; Zamzam Muttaqin; Fiqra Nazib (Advances In Education Journal, 2024)
This study aims to examine the literature on the role of social media in promoting religious moderation. It employs a Systematic Literature Review (SLR) method, involving stages such as theme identification, literature search, selection, analysis, interpretation, drafting, and dissemination of findings. The research is based on 20 articles chosen from a pool of 35 articles published between 2019 and 2024. The study focuses on three key areas: the implications, the role of moderation, and the use of social media in reinforcing religious moderation. The findings of the research reveal that: 1) social media is used with several objectives to strengthen moderation, 2) the benefits of social media in fostering religious moderation are diverse, and 3) there are various implementations or practices in using social media to promote religious moderation, particularly in Indonesia.